Human keratinocytes are a major source of cutaneous platelet-derived growth factor. - Ansel, J C (1993)
PDGF has been implicated as one of the principal mitogens involved in cutaneous wound healing. While it has been previously reported that both platelets and monocytes are a source of PDGF in human dermal wound repair, the production of PDGF by human keratinocytes has not yet been described. In this manuscript, we report the production of PDGF by cultured human keratinocytes. Both PDGF A and B chain mRNA can be detected in cultured cells. While only PDGF-AA polypeptide is found in significant levels in keratinocyte-conditioned culture media, all three PDGF isoforms (AA, AB, and BB) are present in detergent-solubilized cell extracts. No evidence of PDGF receptor expression was observed in cultured keratinocytes when analyzed for either mRNA levels or polypeptide expression, suggesting that PDGF does not play an autocrine role in keratinocyte growth. Analysis of cryosections of human cutaneous wounds by immunostaining for PDGF showed that both PDGF A and B chain is constitutively expressed in normal epidermis, as well as in newly reconstituted wound epidermis. No evidence for PDGF receptor polypeptide expression in the epidermis was detected by immunostaining of cryosections.